Unintended Consequences: A Critical Analysis of Nepals Rape Law Reform and Its Impact on Juvenile Justice - Atreya, Alok; Acharya, Apurba; Paudel, Sudip; Nepal, Samata (Journal of Nepal Health Research Council, 2024)
The increase of the age of consent to 18, with the Muluki Penal Code that came into effect in 2017, created an unintended burden on the juvenile justice system in Nepal. The amendment, drafted to protect minors from sexual exploitation by adults, resulted in the criminalisation of consensual relationships between adolescents. The surge of inmates aged 16 to 18 years is leading Nepal into a crisis in its juvenile correction centres, with overcrowded facilities, decrepit conditions, and increased violence. This crisis was underlined by three deaths in juvenile correction centres at Bhaktapur, Parsa, and Banke up to September 2023. This article explores the legal, social, and ethical dilemmas generated by Nepal's reforms of rape law and advocates for a more nuanced approach in safeguarding vulnerable populations without moralising normal adolescent sexual conduct. This approach is based on the consideration of pending challenges for the juvenile justice system and the development of strategies to reconcile child protection goals with the realities of adolescents' relationships.Keywords: Informed consent; juvenile delinquency; Nepal; rape.